Assessment of Early Warning System and Public Awareness of Floods in Kabul City - Mushwani, Hayatullah; Hashimi , Sayed Kazim; Sahak, Kawoon (Journal of Natural Sciences – Kabul University, 2021)
Floods are natural disasters that occur in various seasons in different districts of Kabul city, causing casualties and financial losses. This research aims to evaluate the effectiveness of the early warning system and the level of public awareness regarding floods in Kabul city. Data for the study were collected using validated questionnaires, alongside a review of relevant books and international journals. The findings reveal a low level of public awareness about flood warnings in Kabul city. This research concludes by recommending the proper implementation of an early warning system to improve flood management significantly.